Midlife milk consumption and substantia nigra neuron density at death. (9th February 2016) - Abbott, Robert D.; Ross, G. Webster; Petrovitch, Helen; Masaki, Kamal H.; Launer, Lenore J.; Nelson, James S.; White, Lon R.; Tanner, Caroline M.
Abstract : Objective: To examine the relationship between midlife milk intake and Parkinson disease (PD) incidence through associations with substantia nigra (SN) neuron density and organochlorine pesticide exposure in decedent brains from the Honolulu-Asia Aging Study. Methods: Milk intake data were collected from 1965 to 1968 in 449 men aged 45–68 years with postmortem examinations from 1992 to 2004. Neuron density (count/mm 2 ) was measured in quadrants from a transverse section of the SN. Additional measures included brain residues of heptachlor epoxide, an organochlorine pesticide found at excessively high levels in the milk supply in Hawaii in the early 1980s. Results: Neuron density was lowest in nonsmoking decedents who consumed high amounts of milk (>16 oz/d). After removing cases of PD and dementia with Lewy bodies, adjusted neuron density in all but the dorsomedial quadrant was 41.5% lower for milk intake >16 oz/d vs intake that was less (95% confidence interval 22.7%–55.7%, p < 0.001). Among those who drank the most milk, residues of heptachlor epoxide were found in 9 of 10 brains as compared to 63.4% (26/41) for those who consumed no milk ( p = 0.017). For those who were ever smokers, an association between milk intake and neuron density was absent. Conclusions: Milk intake is associated with SN neuron loss in decedent brains unaffected by PD. Whether contamination of milk with organochlorine pesticides has a role in SN neurodegeneration warrants further study.